The Sensitivity and Specificity of Chicago Sky Blue (CSB) Dye in Comparisson with Potassium Hydroxide (KOH) Method for Superficial Dermatomycosis - Amalia Nadiasari; Diana Tri Ratnasari; Masfufatun Masfufatun (Berkala Kedokteran, 2020)
Abstract: Superficial dermatomycosis is a skin, nail and hair infection caused by fungal pathogen. Based on the pathogen, this infection can be divided into dermatophytosis, pityriasis versicolor and superficial candidiasis. The rapid and proper diagnosis is necessary to determine the initial theraphy and prevent the treatment delay. Superficial dermatomycosis diagnosis can be performed using anamnesis, physical examination or supporting investigation. The routine investigation method commonly use Potassium Hydroxide (KOH) because the KOH method is easy to be performed, rapid, simple and affordable. Chicago Sky Blue (CSB) is a dye to give a better color contrast to the fungi so the fungi would be easier to be detected. Objectives of this research is to observe the sensitivity and specifity difference of Chicago Sky Blue (CSB) dye and Potassium Hydroxide (KOH) methods for Superficial Dermatomycosis. The research was performed using cross sectional design analitical obsevation with 30 research subjects. The subjects consist of 15 superficial dermatomycosis patients and 15 non-superficial dermatomycosis patients. The samples were taken from the patients lesion swabs. The samples were checked using KOH and CSB, then observed by the medical analyst. The superficial dermatomycosis samples consist of mostly dermathophytosis (53.33%), then pityriasis versicolor (26.67%) and superficial candidiasis (20%). The sensitivity and specificity of KOH were 86.67% and 100%, respectively. The sensitivity and specificity of CSB were 93.33% and 100%, respectively. The CSB dye method has a higher sensitivity than KOH. The fungal elements are nicely dyed and more easily detected using CSB dye.  Keywords: KOH, Chicago Sky Blue, sensitivity, specificity, superficial dermatomycosis